FAKTOR PERILAKU KEPATUHAN PENGGUNAAN APD PADA PEKERJA PT X - Siti Aifatus Solekhah (Universitas Airlangga, 2018)
Behavior was an actual and concrete attitude of one individual toward other individuals. Health and safety at work and its healthy surrounding were assets which high valued for individual, community and country. Personal Protective Equipments (PPE) was a set of tools that workers use to protect some or all part of the body from potential work accident. Workers’ obedience of using PPE had high probability to decrease risk of occupational accident and illness. PT. X was a company that produces all kind of automotive components where there would be a lot of potential work accident from production process, such as fire, explosion, heat and electrical hazard. The attempts to prevent and reduce accident at work in PT. X were safety program called Behavior Based Safety (BBS) and patrol program by Environmental Health System and General of Affair Operational (EHS & GA). The purposes of those programs were for the betterment of Health and Safety Management System and to minimize the number of accident at work.